High-voltage insulated battery management FPC and preparation method thereof
Patent Information
- Application Number
- CN202611339626.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]目前提升FPC高压绝缘性能的主要途径包括增加覆盖膜厚度和在覆盖膜与线路间增设绝缘胶层;增加覆盖膜厚度虽可在一定程度上提升耐压等级,但会导致FPC整体刚度增大,丧失柔性互连的优势,且无法从根本上解决铜线路边缘的电场集中问题;增设绝缘胶层则面临界面增多、气隙风险加大以及高低温冲击下界面脱粘的难题
[0028]综上所述,由于采用了上述技术方案,本发明的有益效果为,
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic materials technology, specifically to a high-voltage insulating FPC for battery management and its preparation method. Background Technology
[0002] Flexible printed circuit boards (FPCs) for battery management serve as core interconnecting components for voltage acquisition, temperature monitoring, and equalization control in new energy vehicle battery packs. Their high-voltage insulation reliability directly determines the safe operation of the battery pack. With the widespread adoption of 800V high-voltage platforms, the potential difference between adjacent conductors of the FPC and between high-voltage nodes and ground has increased significantly. Existing insulation solutions using polyimide capping films and acrylic adhesives can generate electric field concentration at the edges of copper lines under high electric fields, inducing partial discharge and gradually developing into insulation breakdown. At the same time, the adhesive layer will age and generate air gaps under high temperature, high humidity, and temperature cycling conditions, further reducing the partial discharge initiation voltage and seriously threatening the insulation safety of the battery pack.
[0003] Currently, the main approaches to improving the high-voltage insulation performance of FPCs include increasing the thickness of the cover film and adding an insulating adhesive layer between the cover film and the circuit. While increasing the cover film thickness can improve the withstand voltage rating to some extent, it leads to an increase in the overall stiffness of the FPC, losing the advantage of flexible interconnection, and cannot fundamentally solve the problem of electric field concentration at the edge of the copper circuit. Adding an insulating adhesive layer, on the other hand, faces the challenges of increased interfaces, increased air gap risk, and interface debonding under high and low temperature shocks. Therefore, there is an urgent need to develop a high-voltage insulating FPC for battery management that can actively regulate the electric field distribution, eliminate air gaps within the insulation layer, and maintain high interfacial bonding reliability under harsh operating conditions, as well as its fabrication method.
[0004] To address the above problems, the present invention provides a solution. Summary of the Invention
[0005] The purpose of this invention is to provide a high-voltage insulated battery management FPC and its preparation method, which can achieve the synergy of active electric field regulation of high-voltage insulation structure, air gap-free integrated packaging and high interface bonding reliability, while endowing the FPC with partial discharge self-suppression function.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: a high-voltage insulated FPC for battery management, based on an FPC circuit substrate and a gradient dielectric ring gate insulating substrate, wherein the gradient dielectric ring gate insulating substrate is the core insulating structure carrier, the gradient dielectric ring gate insulating substrate is provided with a concentric ring gate structure, and the concentric ring gate structure is partitioned and filled by gradient functional dielectric slurry with different dielectric properties in cooperation with the gradient dielectric ring gate insulating substrate, and then subjected to vacuum degassing and low-temperature thermal curing treatment to form an insulating encapsulation structure with gradient dielectric distribution and surface hydrophobic shielding function, thereby obtaining a high-voltage insulated FPC for battery management;
[0007] Furthermore, the gradient dielectric ring gate insulating matrix is composed of the following components by mass percentage: 84.3485% vinyl-terminated polydimethylsiloxane, 4.5% fumed silica, 3% polymethylhydrosiloxane, 2.5% perfluorodecyltrimethoxysilane, 0.0015% caster platinum catalyst, 0.15% 1-ethynyl-1-cyclohexanol, 1.5% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 1% tris(2,4-di-tert-butylphenyl) phosphite;
[0008] Furthermore, the method for preparing the gradient dielectric ring gate insulating substrate includes the following steps:
[0009] A1: Vinyl-terminated polydimethylsiloxane is placed in a vacuum drying oven at a temperature of 80-100℃ and a vacuum of -0.08 to -0.10 MPa for 4-6 hours to obtain dried vinyl-terminated polydimethylsiloxane. Fumed silica is placed in a vacuum drying oven at a temperature of 100-120℃ and a vacuum of -0.08 to -0.10 MPa for 4-6 hours to obtain dried fumed silica. Polymethylhydrosiloxane is placed in a vacuum drying oven at a temperature of 60-80℃ and a vacuum of -0.08 to -0.10 MPa for 4-6 hours to obtain dried polymethylhydrosiloxane. 1-Ethynyl-1-cyclohexanol is placed in a vacuum drying oven at a temperature of 40-60℃ and a vacuum of -0.08 to -0.10 MPa for 2-4 hours to obtain dried 1-ethynyl-1-cyclohexanol.
[0010] A2: Add dried vinyl-terminated polydimethylsiloxane and dried fumed silica to a planetary mixer, set the stirring speed to 500-800 rpm, and the stirring time to 10-15 min to obtain a silicone rubber base material. Then add dried polymethylhydrosiloxane, Castel platinum catalyst, dried 1-ethynyl-1-cyclohexanol, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl) phosphite to the planetary mixer, set the stirring speed to 800-1200 rpm, and the stirring time to 20-30 min. After stirring, vacuum degassing is performed for 10-15 min under a vacuum degree of -0.08 to -0.10 MPa to obtain a liquid silicone rubber premix.
[0011] A3: Liquid silicone rubber premix is evenly coated onto the surface of release PET film using a precision scraper. The scraper gap is set to 0.3-0.5mm, and the scraper speed is 1-3m / min. After coating, the coated film is sent into a multi-stage hot air oven for gradient pre-curing. The temperature of the first stage is set to 80-90℃ and the dwell time is 5-8min; the temperature of the second stage is set to 100-110℃ and the dwell time is 5-8min; and the temperature of the third stage is set to 115-125℃ and the dwell time is 5-9min. A transition zone with a length of 20-30cm is provided between each stage. After gradient pre-curing, the coated film is allowed to cool naturally to room temperature. The release PET film is then peeled off to obtain a transparent silicone rubber film with a thickness of 0.3-0.5mm.
[0012] A4: A transparent silicone rubber film is laid flat on a laser processing platform. A high-precision hollowing process is performed using an ultraviolet picosecond laser. The laser wavelength is set to 355nm, the pulse width to 10-15ps, the repetition frequency to 500-800kHz, and the cutting speed to 300-600mm / s. The laser focus is set on the middle plane of the transparent silicone rubber film in the thickness direction to process a concentric ring grid pattern. The ring grid consists of three concentric rings with a width of 0.15-0.25mm and a spacing of 0.4-0.7mm. Each concentric ring is connected and fixed to the others by four connecting bridges that are symmetrically distributed at 90°. The connecting bridges connect local areas of adjacent ring grids. The remaining areas between adjacent ring grids, except for the connecting bridges, are hollow ring grid grooves. After processing, the processing surface is blown with compressed air of 0.3-0.5MPa to remove processing debris, and a ring grid structure silicone rubber matrix is obtained.
[0013] A5: The ring-grid structure silicone rubber substrate is placed in a plasma treatment device, and the surface of the ring-grid structure silicone rubber substrate is cleaned and activated online using low-pressure plasma in an argon-oxygen mixed atmosphere. The treatment power is set to 200-400W, the argon flow rate is 80sccm, the oxygen flow rate is 20sccm, the treatment pressure is 20-50Pa, and the treatment time is 60-120s to obtain a surface-activated ring-grid structure silicone rubber substrate.
[0014] A6: Add perfluorodecyltrimethoxysilane to anhydrous ethanol and stir at 300 rpm for 15 min. Then add deionized water and continue stirring and hydrolyzing for 30-60 min while maintaining the stirring speed to obtain a substrate surface treatment solution. The mass ratio of perfluorodecyltrimethoxysilane, anhydrous ethanol and deionized water is 2:90:8. Let the substrate surface treatment solution stand at room temperature for 30-60 min to obtain an aged substrate surface treatment solution.
[0015] A7: Immerse the surface-activated ring-gate structure silicone rubber matrix in an aging substrate surface treatment solution. Set the immersion temperature to 25-35℃ and the immersion time to 60-120s. After immersion, place the ring-gate structure silicone rubber matrix in an oven. Set the temperature to 100-120℃ and dry and cure for 30-45min to obtain a surface-fluorinated ring-gate structure silicone rubber matrix. Place the surface-fluorinated ring-gate structure silicone rubber matrix in a vacuum oven. Set the temperature to 120-140℃, the vacuum degree to -0.08 to -0.10MPa, and the curing time to 30-45min. After curing, allow it to cool naturally to room temperature in the oven to obtain a gradient dielectric ring-gate insulating matrix.
[0016] Furthermore, the vinyl-terminated polydimethylsiloxane has a viscosity of 5000 mPa·s and a vinyl content of 0.3 mmol / g; the polymethylhydrosiloxane has a hydrogen content of 0.3 wt%.
[0017] Furthermore, a method for preparing a high-voltage insulated FPC for battery management includes the following steps:
[0018] S1: Select an FPC circuit substrate, lay the FPC circuit substrate flat on the inspection table, and check the integrity of the circuit and surface defects under an inspection light source with an illuminance of 1200lx. After confirming that there are no open circuits, short circuits and residual copper defects, place the FPC circuit substrate in a plasma treatment device. Use argon-oxygen mixed atmosphere low-pressure plasma to perform online cleaning and activation treatment on the high-voltage pads and surrounding areas of the FPC circuit substrate surface. Set the treatment power to 200-400W, argon flow rate to 80sccm, oxygen flow rate to 20sccm, treatment pressure to 20-50Pa, and treatment time to 60-120s to obtain a surface-activated FPC substrate.
[0019] S2: Immerse the surface-activated FPC substrate in an anhydrous ethanol solution containing 1 wt% perfluorodecyltrimethoxysilane for 60 seconds. After immersion, place the surface-activated FPC substrate in an oven and set the temperature to 100-120℃ for drying and curing for 30-45 minutes to obtain the interface-activated FPC substrate.
[0020] S3: The gradient dielectric ring gate insulating substrate is precisely aligned and placed on the high voltage pad of the interface activated state FPC substrate using an automatic mounting equipment. During placement, ensure that the geometric center of the gradient dielectric ring gate insulating substrate coincides with the geometric center of the high voltage pad. The alignment accuracy is controlled within ±25um. After mounting, let it stand at room temperature for 5-10 minutes to obtain the pre-assembled body.
[0021] S4: Add the inner layer stress buffer high-K dielectric slurry, the middle layer ring grid filling dielectric slurry, and the outer layer shielding connection conductive slurry to the three independent storage tanks of the three-channel vacuum potting equipment. Set the temperature of the storage tanks to 25-35℃. Perform vacuum degassing on each slurry for 20-30 minutes under a vacuum degree ≤100Pa. After degassing, place the pre-assembled part into the potting chamber of the vacuum potting equipment. Set the vacuum degree of the potting chamber to ≤100Pa to obtain the component to be potted.
[0022] S5: Vacuum potting is performed on the component to be potted. First, the inner layer stress-buffering high-K dielectric slurry is injected into the central area of the gradient dielectric ring grid insulating substrate through the first channel precision dispensing head. The dispensing pressure is set to 0.1-0.3MPa, and the dispensing time is 3-8s. After injection, it is allowed to stand for 5-10 minutes. Then, the middle layer ring grid filling dielectric slurry is injected sequentially into the inner ring grid groove, middle ring grid groove, and outer ring grid groove of the gradient dielectric ring grid insulating substrate through the second channel micro-dispensing system. The dispensing pressure is set to 0.08-0.2MPa. After each ring grid groove is injected, it is allowed to stand for 2-4 minutes. Finally, the outer layer shielding connection conductive slurry is injected into the gradient dielectric through the third channel precision dispensing head. For the lead-out connection area of the outermost ring gate of the ring gate insulating substrate, the dispensing pressure is set to 0.1-0.3MPa and the dispensing time is 2-5s. The lead-out connection area is located outside the outermost ring gate. A reference ground pad is provided on the FPC circuit substrate directly below the lead-out connection area. The gradient dielectric ring gate insulating substrate has a vertical through hole in the lead-out connection area. The vertical through hole penetrates the thickness direction of the gradient dielectric ring gate insulating substrate. The outer layer shielding connection conductive paste fills the reference ground pad on the surface of the FPC circuit substrate through the vertical through hole to form a vertical electrical connection path. After potting, it is left to stand for 10-15 minutes under a vacuum degree ≤100Pa to obtain the potted FPC component.
[0023] S6: Transfer the potted FPC component to an oven for low-temperature thermal curing. Set the curing temperature to 130-150℃ and the curing time to 1-2 hours. After curing, allow the FPC component to cool naturally to room temperature in the oven at a rate of 3-6℃ / min. Remove the component after cooling to below 50℃ to obtain the cured FPC component.
[0024] S7: Lay the cured FPC module flat on the inspection table and check the surface flatness of the insulation structure, the quality of the interface bonding and the integrity of the ring grid structure under an inspection light source with an illuminance of 1200lx. After confirming that there are no bubbles, delamination and broken ring defects, immerse the cured FPC module in the perfluorodecyltrimethoxysilane hydrolysate. The perfluorodecyltrimethoxysilane hydrolysate is prepared by perfluorodecyltrimethoxysilane, anhydrous ethanol and deionized water in a mass ratio of 2:90:8. The immersion time is 60-120s. After immersion, dry and cure at 100-120℃ for 30-45min to form a hydrophobic shielding layer on the outer surface of the encapsulation structure, and obtain a high-voltage insulated FPC for battery management.
[0025] Furthermore, the inner layer stress buffer high-K medium slurry described in step S4 is composed of the following components by mass percentage: 47.8485% vinyl-terminated polydimethylsiloxane, 7% polymethylhydrosiloxane, 38% barium titanate submicron powder with an average particle size of 300 nm and a tetragonal phase, 3.5% fumed silica, 0.0015% caster platinum catalyst, 0.15% 1-ethynyl-1-cyclohexanol, 2% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 1% tris(2,4-di-tert-butylphenyl) phosphite;
[0026] The intermediate-layer ring-type gate-filled medium slurry described in step S4 consists of the following components by mass percentage: 53.3485% vinyl-terminated polydimethylsiloxane, 6% polymethylhydrosiloxane, 29% fumed silica, 4% precipitated silica, 0.0015% caster platinum catalyst, 0.15% 1-ethynyl-1-cyclohexanol, 2.5% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 1% tris(2,4-di-tert-butylphenyl) phosphite;
[0027] The outer shielding conductive paste described in step S4 consists of the following components by mass percentage: 48.3485% vinyl-terminated polydimethylsiloxane, 6% polymethylhydrosiloxane, and 40% flake silver powder, with an average particle size of 10 μm and a tap density of 4 g / cm³. 3 The composition includes flake silver powder, 3.5% fumed silica, 0.0015% castor platinum catalyst, 0.15% 1-ethynyl-1-cyclohexanol, 1% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 1% tris(2,4-di-tert-butylphenyl) phosphite.
[0028] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are as follows:
[0029] 1. This invention utilizes the synergistic effect of the concentric ring grid structure of the gradient dielectric ring grid insulating substrate and the partitioned filling of the gradient functional dielectric paste to construct a gradient dielectric distribution that gradually decreases from the center of the high-voltage pad to the outer periphery. The inner layer stress-buffered high-K dielectric paste adheres closely to the high-voltage pad to eliminate the interface air gap and pull the electric field together. The middle layer ring grid filling dielectric paste forms a stepped dielectric constant transition in the three ring grid grooves. The outer layer shielding and connecting conductive paste introduces the residual electric field to the reference ground through vertical through holes, thus solving the problem of large partial discharge caused by electric field concentration in the existing FPC high-voltage insulation scheme.
[0030] 2: This invention achieves a chemical bonding interface between the gradient dielectric ring grid insulation substrate and the FPC circuit substrate through the synergistic effect of plasma activation treatment and perfluorodecyltrimethoxysilane interface anchoring. At the same time, the inner layer stress buffer high-K dielectric slurry adopts a low-modulus vinyl-terminated polydimethylsiloxane system, which absorbs the interfacial thermal stress through elastic deformation when the temperature changes drastically, avoiding interface debonding and insulation failure under high and low temperature shocks, and achieving a balance between high interfacial bonding reliability and long-term operational stability.
[0031] 3: This invention utilizes the synergistic effect of vacuum potting and low-temperature thermosetting. The gradient functional medium slurry is injected into the ring gate groove under vacuum and fully penetrates into the interface micropores. Low-temperature thermosetting enables the slurry to form chemical bonds with the sidewall of the gradient dielectric ring gate insulating substrate and the FPC interface, eliminating air gaps and weak interfaces inside the insulating structure. At the same time, the perfluorodecyltrimethoxysilane hydrolysate impregnation treatment forms a hydrophobic shielding layer on the outer surface of the encapsulation structure, achieving the dual functions of air gap-free integrated encapsulation and surface hydrophobic protection. Detailed Implementation
[0032] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below with reference to specific embodiments.
[0033] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Unless otherwise specified, the materials and reagents used in the following examples are commercially available.
[0034] Example 1
[0035] 1. Place 843.485g of vinyl-terminated polydimethylsiloxane in a vacuum drying oven, set the temperature to 80℃ and the vacuum degree to -0.08MPa, and dry for 4h to obtain 842.8g of dried vinyl-terminated polydimethylsiloxane. Place 45g of fumed silica in a vacuum drying oven, set the temperature to 100℃ and the vacuum degree to -0.08MPa, and dry for 4h to obtain 44.9g of dried fumed silica. Place 30g of polymethylhydrosiloxane in a vacuum drying oven, set the temperature to 60℃ and the vacuum degree to -0.08MPa, and dry for 4h to obtain 29.8g of dried polymethylhydrosiloxane. Place 1.5g of 1-ethynyl-1-cyclohexanol in a vacuum drying oven, set the temperature to 40℃ and the vacuum degree to -0.08MPa, and dry for 2h to obtain 1.4g of dried 1-ethynyl-1-cyclohexanol.
[0036] 2: 842.8g of dried vinyl-terminated polydimethylsiloxane and 44.9g of dried fumed silica were added to a planetary mixer. The mixing speed was set to 500 rpm and the mixing time was 10 min to obtain 887.7g of silicone rubber base material. Subsequently, 29.8g of dried polymethylhydrosiloxane, 0.015g of Castel platinum catalyst, 1.4g of dried 1-ethynyl-1-cyclohexanol, 15g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 10g of tris(2,4-di-tert-butylphenyl) phosphite were added to the planetary mixer. The mixing speed was set to 800 rpm and the mixing time was 20 min. After mixing, vacuum degassing was performed for 10 min under a vacuum degree of -0.08 MPa to obtain 943.9g of liquid silicone rubber premix.
[0037] 3: 943.9g of liquid silicone rubber premix was evenly coated onto the surface of the release PET film using a precision scraper. The scraper gap was set to 0.3mm and the scraper speed to 1m / min. After coating, the coated film was sent into a multi-stage hot air oven for gradient pre-curing. The temperature of the first stage was set to 80℃ and the dwell time to 5min, the temperature of the second stage was set to 100℃ and the dwell time to 5min, and the temperature of the third stage was set to 115℃ and the dwell time to 5min. A transition zone with a length of 20cm was set between each stage. After gradient pre-curing, the coated film was allowed to cool naturally to room temperature. The release PET film was then peeled off to obtain a transparent silicone rubber film with a thickness of 0.3mm and a mass of 938.2g.
[0038] 4: A 938.2g transparent silicone rubber film was laid flat on a laser processing platform. A high-precision hollowing process was performed using an ultraviolet picosecond laser. The laser wavelength was set to 355nm, the pulse width to 10ps, the repetition frequency to 500kHz, and the cutting speed to 300mm / s. The laser focus was set on the middle plane of the transparent silicone rubber film in the thickness direction to process a concentric ring grid pattern. The ring grid consists of three concentric rings with a width of 0.15mm and a spacing of 0.4mm. Each concentric ring is connected and fixed to each other by four connecting bridges that are symmetrically distributed at 90°. The connecting bridges connect local areas of adjacent ring grids. The remaining areas between adjacent ring grids, except for the connecting bridges, are hollow ring grid grooves. After processing, the processing surface was blown with 0.3MPa compressed air to remove processing debris, resulting in an 856.4g ring grid structure silicone rubber matrix.
[0039] 5: 856.4g of ring-grid structured silicone rubber matrix was placed in a plasma treatment device, and the surface of the ring-grid structured silicone rubber matrix was cleaned and activated online using low-pressure plasma in an argon-oxygen mixed atmosphere. The treatment power was set to 200W, the argon flow rate to 80sccm, the oxygen flow rate to 20sccm, the treatment pressure to 20Pa, and the treatment time to 60s, resulting in 855.8g of surface-activated ring-grid structured silicone rubber matrix.
[0040] 6: Add 25g of perfluorodecyltrimethoxysilane to 1125g of anhydrous ethanol and stir at 300rpm for 15min. Then add 100g of deionized water and continue stirring for 30min while maintaining the same speed to hydrolyze the solution, resulting in 1250g of substrate surface treatment solution. Allow the substrate surface treatment solution to stand at room temperature for 30min to age, resulting in 1250g of aged substrate surface treatment solution.
[0041] 7: 855.8g of surface-activated ring-gate structure silicone rubber matrix was immersed in 1000g of aged matrix surface treatment solution. The immersion temperature was set to 25℃ and the immersion time was 60s. After immersion, the ring-gate structure silicone rubber matrix was placed in an oven at 100℃ and dried and cured for 30min to obtain a surface-fluorinated ring-gate structure silicone rubber matrix. The surface-fluorinated ring-gate structure silicone rubber matrix was then placed in a vacuum oven at 120℃ and a vacuum degree of -0.08MPa for 30min. After curing, the matrix was allowed to cool naturally to room temperature in the oven to obtain 858.2g of the gradient dielectric ring-gate insulating matrix prepared in Example 1.
[0042] Example 2
[0043] 1. Place 843.485g of vinyl-terminated polydimethylsiloxane in a vacuum drying oven, set the temperature to 100℃ and the vacuum degree to -0.10MPa, and dry for 6h to obtain 842.1g of dried vinyl-terminated polydimethylsiloxane. Place 45g of fumed silica in a vacuum drying oven, set the temperature to 120℃ and the vacuum degree to -0.10MPa, and dry for 6h to obtain 44.5g of dried fumed silica. Place 30g of polymethylhydrosiloxane in a vacuum drying oven, set the temperature to 80℃ and the vacuum degree to -0.10MPa, and dry for 6h to obtain 29.4g of dried polymethylhydrosiloxane. Place 1.5g of 1-ethynyl-1-cyclohexanol in a vacuum drying oven, set the temperature to 60℃ and the vacuum degree to -0.10MPa, and dry for 4h to obtain 1.3g of dried 1-ethynyl-1-cyclohexanol.
[0044] 2: 842.1g of dried vinyl-terminated polydimethylsiloxane and 44.5g of dried fumed silica were added to a planetary mixer. The mixing speed was set to 800 rpm and the mixing time was 15 min to obtain 886.6g of silicone rubber base material. Subsequently, 29.4g of dried polymethylhydrosiloxane, 0.015g of Castel platinum catalyst, 1.3g of dried 1-ethynyl-1-cyclohexanol, 15g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 10g of tris(2,4-di-tert-butylphenyl) phosphite were added to the planetary mixer. The mixing speed was set to 1200 rpm and the mixing time was 30 min. After mixing, vacuum degassing was performed for 15 min under a vacuum degree of -0.10 MPa to obtain 942.3g of liquid silicone rubber premix.
[0045] 3: 942.3g of liquid silicone rubber premix was evenly coated onto the surface of the release PET film using a precision scraper. The scraper gap was set to 0.5mm and the scraper speed to 3m / min. After coating, the coated film was sent into a multi-stage hot air oven for gradient pre-curing. The temperature of the first stage was set to 90℃ and the dwell time to 8min, the temperature of the second stage was set to 110℃ and the dwell time to 8min, and the temperature of the third stage was set to 125℃ and the dwell time to 9min. A transition zone with a length of 30cm was set between each stage. After gradient pre-curing, the coated film was allowed to cool naturally to room temperature. The release PET film was then peeled off to obtain a transparent silicone rubber film with a thickness of 0.5mm and a mass of 933.5g.
[0046] 4: A 933.5g transparent silicone rubber film was laid flat on a laser processing platform. A high-precision hollowing process was performed using an ultraviolet picosecond laser. The laser wavelength was set to 355nm, the pulse width to 15ps, the repetition frequency to 800kHz, and the cutting speed to 600mm / s. The laser focus was set on the middle plane of the transparent silicone rubber film in the thickness direction to process a concentric ring grid pattern. The ring grid consists of three concentric rings with a width of 0.25mm and a spacing of 0.7mm. Each concentric ring is connected and fixed to each other by four connecting bridges that are symmetrically distributed at 90°. The connecting bridges connect local areas of adjacent ring grids. The remaining areas between adjacent ring grids, except for the connecting bridges, are hollow ring grid grooves. After processing, the processing surface was blown with 0.5MPa compressed air to remove processing debris, resulting in 845.3g of ring grid structure silicone rubber matrix.
[0047] 5: 845.3g of ring-grid structured silicone rubber matrix was placed in a plasma treatment device, and the surface of the ring-grid structured silicone rubber matrix was cleaned and activated online using low-pressure plasma in an argon-oxygen mixed atmosphere. The treatment power was set to 400W, the argon flow rate to 80sccm, the oxygen flow rate to 20sccm, the treatment pressure to 50Pa, and the treatment time to 120s, resulting in 844.5g of surface-activated ring-grid structured silicone rubber matrix.
[0048] 6: Add 25g of perfluorodecyltrimethoxysilane to 1125g of anhydrous ethanol and stir at 300rpm for 15min. Then add 100g of deionized water and continue stirring and hydrolyzing for 60min while maintaining the same speed to obtain 1250g of substrate surface treatment solution. Let the substrate surface treatment solution stand at room temperature for 60min to obtain 1250g of aged substrate surface treatment solution.
[0049] 7: 844.5g of surface-activated ring-gate structure silicone rubber matrix was immersed in 1000g of aged matrix surface treatment solution. The immersion temperature was set at 35℃ and the immersion time was 120s. After immersion, the ring-gate structure silicone rubber matrix was placed in an oven at 120℃ and dried and cured for 45min to obtain a surface-fluorinated ring-gate structure silicone rubber matrix. The surface-fluorinated ring-gate structure silicone rubber matrix was then placed in a vacuum oven at 140℃ and a vacuum degree of -0.10MPa for 45min. After curing, the matrix was allowed to cool naturally to room temperature in the oven to obtain 847.8g of the gradient dielectric ring-gate insulating matrix prepared in Example 2.
[0050] Example 3
[0051] 1. Select an FPC circuit substrate and lay it flat on an inspection table. Under an inspection light source with an illuminance of 1200 lx, check the integrity of the circuit and surface defects. After confirming that there are no open circuits, short circuits, or residual copper defects, place the FPC circuit substrate in a plasma treatment device. Use an argon-oxygen mixed atmosphere low-pressure plasma to perform online cleaning and activation treatment on the high-voltage pads and surrounding areas of the FPC circuit substrate. Set the treatment power to 200W, the argon flow rate to 80 sccm, the oxygen flow rate to 20 sccm, the treatment pressure to 20-50 Pa, and the treatment time to 60 s to obtain a surface-activated FPC substrate.
[0052] 2: Immerse the surface-activated FPC substrate in an anhydrous ethanol solution containing 1 wt% perfluorodecyltrimethoxysilane for 60 seconds. After immersion, place the surface-activated FPC substrate in an oven at 100°C and dry for 30 minutes to obtain the interface-activated FPC substrate.
[0053] 3: The gradient dielectric ring gate insulating substrate prepared in Example 1 is precisely aligned and placed on the high voltage pad of the interface activated state FPC substrate using an automatic mounting equipment. During placement, it is ensured that the geometric center of the gradient dielectric ring gate insulating substrate coincides with the geometric center of the high voltage pad. The alignment accuracy is controlled within ±25um. After mounting, the substrate is left to stand at room temperature for 5 minutes to obtain a pre-assembled body.
[0054] 4: Add the inner layer stress-buffering high-K dielectric slurry, the middle layer ring grid filling dielectric slurry, and the outer layer shielding connection conductive slurry to the three independent storage tanks of the three-channel vacuum potting equipment. Set the temperature of the storage tanks to 25℃ and perform vacuum degassing on each slurry for 20 minutes under a vacuum degree ≤100Pa. After degassing, place the pre-assembled part into the potting chamber of the vacuum potting equipment and set the vacuum degree of the potting chamber to ≤100Pa to obtain the component to be potted.
[0055] 5. Vacuum potting is performed on the component to be potted. First, the inner layer stress-buffering high-K dielectric slurry is injected into the central area of the gradient dielectric ring grid insulation substrate through the first channel precision dispensing head. The dispensing pressure is set to 0.1 MPa and the dispensing time is 3 seconds. After injection, it is allowed to stand for 5 minutes. Then, the middle layer ring grid filling dielectric slurry is injected into the inner ring grid groove, middle ring grid groove, and outer ring grid groove of the gradient dielectric ring grid insulation substrate sequentially through the second channel micro-dispensing system. The dispensing pressure is set to 0.08 MPa. After each ring grid groove is injected, it is allowed to stand for 2 minutes. Finally, the outer layer shielding connection conductive slurry is injected into the gradient dielectric ring grid insulation substrate through the third channel precision dispensing head. The lead-out connection area of the outermost ring gate of the substrate is set with a dispensing pressure of 0.1MPa and a dispensing time of 2s. The lead-out connection area is located outside the outermost ring gate. A reference ground pad is provided on the FPC circuit substrate directly below the lead-out connection area. The gradient dielectric ring gate insulating substrate has a vertical through hole in the lead-out connection area. The vertical through hole penetrates the thickness direction of the gradient dielectric ring gate insulating substrate. The outer layer shielding connection conductive paste fills the reference ground pad on the surface of the FPC circuit substrate through the vertical through hole to form a vertical electrical connection path. After potting, it is left to stand for 10 minutes under a vacuum degree ≤100Pa to obtain the potted FPC component.
[0056] 6: Transfer the potted FPC component to an oven for low-temperature thermosetting. Set the curing temperature to 130℃ and the curing time to 1 hour. After curing, allow the FPC component to cool naturally to room temperature in the oven at a rate of 3℃ / min. Remove the component after cooling to below 50℃ to obtain the cured FPC component.
[0057] 7. The cured FPC module is laid flat on the inspection table. Under an inspection light source with an illuminance of 1200 lx, the surface flatness of the insulation structure, the quality of the interface bonding, and the integrity of the ring grid structure are checked. After confirming that there are no bubbles, delamination, or broken ring defects, 25 g of perfluorodecyltrimethoxysilane is added to 1125 g of anhydrous ethanol and stirred and dispersed at 300 rpm for 15 min. Then, 100 g of deionized water is added, and the stirring and hydrolysis are continued for 60 min while maintaining the same speed. 1250 g of perfluorodecyltrimethoxysilane hydrolysate is obtained. The cured FPC module is immersed in the perfluorodecyltrimethoxysilane hydrolysate for 60 s. After immersion, it is dried and cured at 100 °C for 30 min to form a hydrophobic shielding layer on the outer surface of the encapsulation structure, thus obtaining the high-voltage insulated battery management FPC prepared in Example 3.
[0058] Example 4
[0059] 1. Select an FPC circuit substrate and lay it flat on an inspection table. Under an inspection light source with an illuminance of 1200 lx, check the integrity of the circuit and surface defects. After confirming that there are no open circuits, short circuits, or residual copper defects, place the FPC circuit substrate in a plasma treatment device. Use an argon-oxygen mixed atmosphere low-pressure plasma to perform online cleaning and activation treatment on the high-voltage pads and surrounding areas of the FPC circuit substrate surface. Set the treatment power to 400W, the argon flow rate to 80 sccm, the oxygen flow rate to 20 sccm, the treatment pressure to 50 Pa, and the treatment time to 120 s to obtain a surface-activated FPC substrate.
[0060] 2: Immerse the surface-activated FPC substrate in an anhydrous ethanol solution containing 1 wt% perfluorodecyltrimethoxysilane for 60 seconds. After immersion, place the surface-activated FPC substrate in an oven at 120°C and dry and cure for 45 minutes to obtain the interface-activated FPC substrate.
[0061] 3: The gradient dielectric ring gate insulating substrate prepared in Example 2 is precisely aligned and placed on the high voltage pad of the interface activated state FPC substrate using an automatic mounting equipment. During placement, it is ensured that the geometric center of the gradient dielectric ring gate insulating substrate coincides with the geometric center of the high voltage pad. The alignment accuracy is controlled within ±25um. After mounting, the substrate is left to stand at room temperature for 10 minutes to obtain a pre-assembled body.
[0062] 4: Add the inner layer stress buffer high-K dielectric slurry, the middle layer ring grid filling dielectric slurry, and the outer layer shielding connection conductive slurry to the three independent storage tanks of the three-channel vacuum potting equipment. Set the temperature of the storage tanks to 35℃ and perform vacuum degassing on each slurry for 30 minutes under a vacuum degree ≤100Pa. After degassing, place the pre-assembled part into the potting chamber of the vacuum potting equipment and set the vacuum degree of the potting chamber to ≤100Pa to obtain the component to be potted.
[0063] 5. Vacuum potting is performed on the component to be potted. First, the inner layer stress-buffering high-K dielectric slurry is injected into the central area of the gradient dielectric ring gate insulation substrate through the first channel precision dispensing head. The dispensing pressure is set to 0.3 MPa and the dispensing time is 8 seconds. After injection, it is allowed to stand for 10 minutes. Then, the middle layer ring gate filling dielectric slurry is injected into the inner ring gate groove, middle ring gate groove, and outer ring gate groove of the gradient dielectric ring gate insulation substrate sequentially through the second channel micro-dispensing system. The dispensing pressure is set to 0.2 MPa. After each ring gate groove is injected, it is allowed to stand for 4 minutes. Finally, the outer layer shielding connection conductive slurry is injected into the gradient dielectric ring gate insulation substrate through the third channel precision dispensing head. The lead-out connection area of the outermost ring gate of the substrate is set with a dispensing pressure of 0.3MPa and a dispensing time of 5s. The lead-out connection area is located outside the outermost ring gate. A reference ground pad is provided on the FPC circuit substrate directly below the lead-out connection area. The gradient dielectric ring gate insulating substrate has a vertical through hole in the lead-out connection area. The vertical through hole penetrates the thickness direction of the gradient dielectric ring gate insulating substrate. The outer layer shielding connection conductive paste fills the reference ground pad on the surface of the FPC circuit substrate through the vertical through hole to form a vertical electrical connection path. After potting, it is left to stand for 15 minutes under a vacuum degree ≤100Pa to obtain the potted FPC component.
[0064] 6: Transfer the potted FPC component to an oven for low-temperature thermosetting. Set the curing temperature to 150℃ and the curing time to 2h. After curing, allow the FPC component to cool naturally to room temperature in the oven at a cooling rate of 6℃ / min. Remove the component after cooling to below 50℃ to obtain the cured FPC component.
[0065] 7. The cured FPC module was laid flat on the inspection table. Under an inspection light source with an illuminance of 1200 lx, the surface flatness of the insulation structure, the quality of the interface bonding, and the integrity of the ring grid structure were checked. After confirming that there were no bubbles, delamination, or broken ring defects, 25 g of perfluorodecyltrimethoxysilane was added to 1125 g of anhydrous ethanol and stirred and dispersed at 300 rpm for 15 min. Then, 100 g of deionized water was added, and the stirring and hydrolysis were continued for 60 min while maintaining the same speed. 1250 g of perfluorodecyltrimethoxysilane hydrolysate was obtained. The cured FPC module was immersed in the perfluorodecyltrimethoxysilane hydrolysate for 120 s. After immersion, it was dried and cured at 120 °C for 45 min to form a hydrophobic shielding layer on the outer surface of the encapsulation structure. The high-voltage insulated battery management FPC prepared in Example 4 was obtained.
[0066] Comparative Example 1
[0067] The difference between this comparative example and Example 3 is that the gradient dielectric ring gate insulating substrate prepared in Example 1 is replaced with a commercially available ordinary silicone rubber gasket, while the other components and processes remain unchanged.
[0068] The commercially available ordinary silicone rubber gasket is made of methyl vinyl silicone rubber with a thickness of 0.3 mm. Its outer diameter is the same as that of the gradient dielectric ring grid insulating substrate prepared in Example 1, and its inner diameter is the diameter of the central region of the gradient dielectric ring grid insulating substrate. The gasket surface has no ring grid structure.
[0069] The specific preparation method is as follows:
[0070] 1. Select an FPC circuit substrate and lay it flat on an inspection table. Under an inspection light source with an illuminance of 1200 lx, check the integrity of the circuit and surface defects. After confirming that there are no open circuits, short circuits, or residual copper defects, place the FPC circuit substrate in a plasma treatment device. Use low-pressure plasma in an argon-oxygen mixed atmosphere to perform online cleaning and activation treatment on the high-voltage pads and surrounding areas of the FPC circuit substrate. Set the treatment power to 200W, the argon flow rate to 80 sccm, the oxygen flow rate to 20 sccm, the treatment pressure to 20 Pa, and the treatment time to 60 s to obtain a surface-activated FPC substrate.
[0071] 2: Immerse the surface-activated FPC substrate in an anhydrous ethanol solution containing 1 wt% perfluorodecyltrimethoxysilane for 60 seconds. After immersion, place the surface-activated FPC substrate in an oven at 100°C and dry for 30 minutes to obtain the interface-activated FPC substrate.
[0072] 3: Place a commercially available ordinary silicone rubber gasket on the high-voltage pad of the interface-activated FPC substrate using an automatic mounting device. During placement, ensure that the geometric center of the commercially available ordinary silicone rubber gasket coincides with the geometric center of the high-voltage pad. The alignment accuracy is controlled within ±25um. After mounting, let it stand at room temperature for 5 minutes to obtain the pre-assembled body.
[0073] 4: Add the inner layer stress-buffering high-K dielectric slurry, the middle layer ring grid filling dielectric slurry, and the outer layer shielding connection conductive slurry to the three independent storage tanks of the three-channel vacuum potting equipment. Set the temperature of the storage tanks to 25℃ and perform vacuum degassing on each slurry for 20 minutes under a vacuum degree ≤100Pa. After degassing, place the pre-assembled part into the potting chamber of the vacuum potting equipment and set the vacuum degree of the potting chamber to ≤100Pa to obtain the component to be potted.
[0074] 5. Vacuum potting is performed on the component to be potted. First, the inner layer stress buffer high-K dielectric slurry is injected into the center area of a commercially available ordinary silicone rubber gasket through the first channel precision dispensing head. The dispensing pressure is set to 0.1MPa and the dispensing time is 3s. After injection, it is allowed to stand for 5min. Then, the middle layer ring grid filling dielectric slurry is injected into the annular gap between the commercially available ordinary silicone rubber gasket and the high voltage pad through the second channel micro-dispensing system. The dispensing pressure is set to 0.08MPa. After injection, it is allowed to stand for 2min. Finally, the outer layer shielding connection conductive slurry is injected into the lead-out connection area around the commercially available ordinary silicone rubber gasket through the third channel precision dispensing head. The dispensing pressure is set to 0.1MPa and the dispensing time is 2s. The lead-out connection area is located on the outside of the commercially available ordinary silicone rubber gasket. A reference ground pad is provided on the FPC circuit substrate directly below the lead-out connection area. After potting, it is allowed to stand for 10min under a vacuum degree ≤100Pa to obtain the potted FPC component.
[0075] 6: Transfer the potted FPC component to an oven for low-temperature thermosetting. Set the curing temperature to 130℃ and the curing time to 1 hour. After curing, allow the FPC component to cool naturally to room temperature in the oven at a rate of 3℃ / min. Remove the component after cooling to below 50℃ to obtain the cured FPC component.
[0076] 7. The cured FPC module was laid flat on the inspection table. Under an inspection light source with an illuminance of 1200 lx, the surface flatness of the insulation structure and the quality of the interface bonding were checked. After confirming that there were no bubbles or delamination defects, 25 g of perfluorodecyltrimethoxysilane was added to 1125 g of anhydrous ethanol and stirred and dispersed at 300 rpm for 15 min. Then, 100 g of deionized water was added and the stirring and hydrolysis were continued for 60 min while maintaining the same speed. 1250 g of perfluorodecyltrimethoxysilane hydrolysate was obtained. The cured FPC module was immersed in the perfluorodecyltrimethoxysilane hydrolysate for 60 s. After immersion, it was dried and cured at 100 °C for 30 min to form a hydrophobic shielding layer on the outer surface of the encapsulation structure. The high-voltage insulated battery management FPC prepared in Comparative Example 1 was obtained.
[0077] Comparative Example 2
[0078] The difference between this comparative example and Example 3 is that the inner layer stress buffer high-K dielectric slurry, the middle layer ring gate filling dielectric slurry, and the outer layer shielding connection conductive slurry are not filled in the ring gate groove of the gradient dielectric ring gate insulating substrate, and the potting process is eliminated, while the remaining components and processes remain unchanged.
[0079] The specific preparation method is as follows:
[0080] 1. Select an FPC circuit substrate and lay it flat on an inspection table. Under an inspection light source with an illuminance of 1200 lx, check the integrity of the circuit and surface defects. After confirming that there are no open circuits, short circuits, or residual copper defects, place the FPC circuit substrate in a plasma treatment device. Use low-pressure plasma in an argon-oxygen mixed atmosphere to perform online cleaning and activation treatment on the high-voltage pads and surrounding areas of the FPC circuit substrate. Set the treatment power to 200W, the argon flow rate to 80 sccm, the oxygen flow rate to 20 sccm, the treatment pressure to 20 Pa, and the treatment time to 60 s to obtain a surface-activated FPC substrate.
[0081] 2: Immerse the surface-activated FPC substrate in an anhydrous ethanol solution containing 1 wt% perfluorodecyltrimethoxysilane for 60 seconds. After immersion, place the surface-activated FPC substrate in an oven at 100°C and dry for 30 minutes to obtain the interface-activated FPC substrate.
[0082] 3: The gradient dielectric ring gate insulating substrate prepared in Example 1 is precisely aligned and placed on the high voltage pad of the interface activated state FPC substrate using an automatic mounting equipment. During placement, it is ensured that the geometric center of the gradient dielectric ring gate insulating substrate coincides with the geometric center of the high voltage pad. The alignment accuracy is controlled within ±25μm. After mounting, the substrate is left to stand at room temperature for 5 minutes to obtain a pre-assembled body.
[0083] 4: Transfer the pre-assembled part to an oven for low-temperature thermosetting. Set the curing temperature to 130℃ and the curing time to 1 hour. After curing, allow the FPC component to cool naturally to room temperature in the oven at a rate of 3℃ / min. Remove it after cooling to below 50℃ to obtain the cured FPC component.
[0084] 5. The cured FPC module was laid flat on the inspection table and its surface integrity was checked under an inspection light source with an illuminance of 1200 lx. After confirming that there were no broken ring defects, 25 g of perfluorodecyltrimethoxysilane was added to 1125 g of anhydrous ethanol and stirred and dispersed at 300 rpm for 15 min. Then, 100 g of deionized water was added and the stirring and hydrolysis were continued for 60 min while maintaining the same speed. 1250 g of perfluorodecyltrimethoxysilane hydrolysate was obtained. The cured FPC module was immersed in the perfluorodecyltrimethoxysilane hydrolysate for 60 s. After immersion, it was dried and cured at 100 °C for 30 min to obtain the high-voltage insulating battery management FPC prepared in Comparative Example 2.
[0085] Partial discharge test
[0086] The high-voltage insulated battery management FPCs prepared in Examples 3, 4, Comparative Example 1, and Comparative Example 2 were used as test samples. After being placed under standard conditions for 24 hours, partial discharge tests were performed according to IEC 60270 "High-voltage test techniques - Partial discharge measurements". The test voltage was 1200V and the test time was 60s. The partial discharge amount was recorded. Each group of samples was tested in parallel 3 times, and the average value was taken and the test results were recorded.
[0087] Table 1. Partial Discharge Test Results
[0088] Test Project Example 3 Example 4 Comparative Example 1 Comparative Example 2 Partial discharge quantity / pC 3.2 2.1 28.6 35.4
[0089] Analysis of Table 1 shows that the partial discharge amounts in Examples 3 and 4 are only 3.2 pC and 2.1 pC, respectively, while the partial discharge amounts in Comparative Examples 1 and 2 reach 28.6 pC and 35.4 pC, respectively, which are 793.8% and 1006.3% higher than those in Example 3. The reason for this is that Examples 3 and 4 use a gradient dielectric ring grid insulating substrate. Its concentric ring grid structure works in conjunction with the gradient functional dielectric paste. The inner layer stress buffer high-K dielectric paste adheres closely to the high voltage pad to eliminate the interface air gap. The middle layer ring grid filling dielectric paste forms a stepped dielectric constant distribution from the inside to the outside in the three ring grid grooves, which effectively homogenizes the concentrated electric field at the edge of the high voltage pad. The outer layer shielding connection conductive paste forms an electrical connection with the reference ground pad through a vertical through hole, which guides the residual electric field to the reference ground. The synergistic effect of the three mechanisms significantly suppresses the occurrence of partial discharge.
[0090] Comparative Example 1 used a commercially available ordinary silicone rubber gasket without a ring gate structure. Relying solely on a single dielectric slurry, it could not form a gradient dielectric distribution, resulting in severe electric field concentration at the edge of the high-voltage pad and a large partial discharge. Comparative Example 2 used the gradient dielectric ring gate insulating substrate prepared in Example 1, but the ring gate groove was not filled with gradient functional dielectric slurry. Instead, the ring gate groove contained air. Air has a low dielectric constant and a breakdown field strength of only 3kV / mm. Under a test voltage of 1200V, the air in the ring gate groove underwent ionization discharge, resulting in the highest partial discharge. This verified the necessity of the synergistic cooperation between the gradient dielectric ring gate insulating substrate and the gradient functional dielectric slurry for achieving active electric field regulation and self-suppression of partial discharge.
[0091] The partial discharge amount in Example 4 was 34.4% lower than that in Example 3. The reason for this is that Example 4 used the maximum process parameters, resulting in higher plasma treatment power and longer treatment time, more complete activation of the FPC substrate surface, higher grafting density of perfluorodecyltrimethoxysilane coupling agent at the interface, tighter interface bonding, further reduction of interfacial micro-gaps, and lower partial discharge amount.
[0092] Insulation withstand voltage test
[0093] The high-voltage insulated battery management FPCs prepared in Examples 3, 4, Comparative Example 1, and Comparative Example 2 were used as test samples. After being placed under standard conditions for 24 hours, insulation withstand voltage tests were performed according to IPC-TM-650 2.5.7 "Dielectric Withstanding Voltage, Flexible Printed Wiring Materials". The test voltage was increased from 0V to 3000V at a rate of 500V / s and held for 60s. Whether breakdown occurred was recorded. Each group of samples was tested in parallel 5 times, and the number of breakdowns and the breakdown voltage were recorded.
[0094] Table 2, Insulation withstand voltage test results
[0095] Test Project Example 3 Example 4 Comparative Example 1 Comparative Example 2 Number of penetrations / 5 times 0 0 3 5 Minimum breakdown voltage / V >3000 >3000 1850 1200
[0096] Analysis of Table 2 shows that Examples 3 and 4 did not break down under a test voltage of 3000V, while Comparative Example 1 broke down in 3 out of 5 tests, with a minimum breakdown voltage of 1850V. Comparative Example 2 broke down in all 5 tests, with a minimum breakdown voltage of only 1200V. The reason for this is that Examples 3 and 4, through vacuum potting and low-temperature thermal curing processes, fully filled and cross-linked the gradient functional dielectric slurry in the ring grid groove, forming chemical bonds with the sidewall of the gradient dielectric ring grid insulating substrate and the FPC interface, achieving a gapless integrated encapsulation. There are no continuous weak interfaces or air gap channels in the insulation structure, resulting in excellent withstand voltage performance.
[0097] Comparative Example 1 uses commercially available ordinary silicone rubber gaskets. The gaskets and high-voltage pads are only filled with slurry, lacking mechanical anchoring and gradient dielectric regulation of the ring grid structure. The interface bonding is weak, and it is easy to cause surface flashover breakdown along the interface under high voltage.
[0098] In Comparative Example 2, the ring grid groove is empty. The air gap will cause breakdown discharge at around 1200V. The ring grid structure itself cannot bear the insulation withstand voltage function alone. This verifies the decisive role of vacuum potting gradient functional medium slurry in achieving gapless integrated encapsulation and high insulation withstand voltage.
[0099] High and low temperature shock reliability test
[0100] The high-voltage insulated battery management FPCs prepared in Examples 3, 4, Comparative Example 1, and Comparative Example 2 were used as test samples. High and low temperature shock tests were conducted according to IPC-TM-650 2.6.7 "Thermal Shock, Flexible Printed Wiring Materials". The high temperature was set at 125°C and the low temperature at -40°C. The high and low temperature transition time was ≤10s. Each temperature point was held for 15min and the cycle was repeated 1000 times.
[0101] After the test, the sample was allowed to recover for 2 hours under standard conditions. The partial discharge quantity was tested according to the method in Table 1, and the insulation withstand voltage was tested according to the method in Table 2. The change rate of partial discharge quantity and the insulation withstand voltage retention rate were calculated. Each group of samples was tested in parallel 3 times, and the average value was taken. The test results were recorded.
[0102] Table 3. High and low temperature shock reliability test results
[0103] Test Project Example 3 Example 4 Comparative Example 1 Comparative Example 2 Partial discharge quantity after impact / pC 4.8 3.0 Breakdown failure Breakdown failure Partial discharge rate of change / % 50.0 42.9 — — Insulation withstand voltage pass rate after impact / % 100 100 0 0
[0104] As shown in Table 3, after 1000 high and low temperature shocks, the partial discharge quantities of Examples 3 and 4 were 4.8 pC and 3.0 pC, respectively, which increased by 50.0% and 42.9% compared with before the shocks, but were still far below the engineering acceptable limit of 10 pC. The insulation withstand voltage pass rate after the shocks was 100%, showing excellent interface bonding reliability.
[0105] Comparative Examples 1 and 2 both failed after impact testing and could not complete the partial discharge quantity test. The reason for this was that in Examples 3 and 4, the gradient dielectric ring grid insulating substrate and the FPC substrate formed a chemically bonded interface anchor through plasma activation treatment and perfluorodecyltrimethoxysilane coupling agent. At the same time, the inner layer stress buffer high-K dielectric slurry adopted a low-modulus vinyl-terminated polydimethylsiloxane system, which can absorb the interfacial thermal stress through elastic deformation when the temperature changes drastically, thus avoiding interface debonding and cracking.
[0106] In Comparative Example 1, the commercially available ordinary silicone rubber gasket had no chemical bonding anchorage with the FPC substrate, and the crosslinking system of the silicone rubber gasket and the slurry was different, resulting in poor interfacial compatibility. Under repeated thermal shock, the interface debonded and delaminated, leading to insulation failure.
[0107] In Comparative Example 2, the ring grid groove was not filled with slurry. The connection bridge between the ring grid skeleton and the FPC substrate broke due to stress concentration under thermal shock, resulting in loss of structural integrity. This verifies the key role of the interface activation and anchoring mechanism of the gradient dielectric ring grid insulating substrate and the synergistic cooperation of the gradient functional medium slurry in achieving high interface bonding reliability.
[0108] The change rate of partial discharge after high and low temperature impact in Example 4 was lower than that in Example 3. The reason for this is that Example 4 used the maximum value of process parameters, with a higher low temperature thermal curing temperature and a longer time, resulting in a higher crosslinking density of the gradient functional medium slurry, better mechanical properties, and stronger resistance to thermal stress.
[0109] Surface hydrophobicity test
[0110] Samples with dimensions of 50 mm × 50 mm were cut from the high-voltage insulating battery management FPCs prepared in Examples 3, 4, Comparative Example 1, and Comparative Example 2. After being placed under standard conditions for 24 hours, the water contact angle of the encapsulation structure surface was tested according to GB / T 30447-2013 "Method for Measurement of Contact Angle of Nanofilms". Each group of samples was tested in parallel 3 times, and the average value was taken and the test results were recorded.
[0111] Table 4. Surface hydrophobicity test results
[0112] Test Project Example 3 Example 4 Comparative Example 1 Comparative Example 2 Water contact angle / ° 116 119 114 115
[0113] As shown in Table 4, the water contact angles of Examples 3, 4, Comparative Example 1, and Comparative Example 2 were 116°, 119°, 114°, and 115°, respectively. All four groups of samples exhibited good hydrophobic properties with small differences in values. The reason for this is that all four groups of samples were impregnated with perfluorodecyltrimethoxysilane hydrolysate. After the hydrolysis and condensation of the fluorinated silane, a low surface energy hydrophobic shielding layer was formed on the outer surface of the encapsulation structure. This treatment process plays a dominant role in the hydrophobic properties.
[0114] The water contact angle of Example 4 is slightly higher. The reason for this is that the immersion time and drying curing time of Example 4 are longer, the grafting density of fluorinated silane on the surface is higher, and the hydrophobic layer is more dense and complete, which verifies the effectiveness and consistency of the surface hydrophobic shielding treatment process.
[0115] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A high-voltage insulated FPC for battery management, characterized in that, Based on FPC circuit substrate and gradient dielectric ring gate insulation substrate, with the gradient dielectric ring gate insulation substrate as the core insulation structure carrier, the gradient dielectric ring gate insulation substrate has a concentric ring gate structure. The concentric ring gate structure is partitioned and filled by gradient functional dielectric slurry with different dielectric properties that cooperate with the gradient dielectric ring gate insulation substrate. After vacuum degassing and low temperature thermosetting treatment, an insulating encapsulation structure with gradient dielectric distribution and surface hydrophobic shielding function is formed, resulting in a high-voltage insulating FPC for battery management.
2. The high-voltage insulated FPC for battery management according to claim 1, characterized in that, The gradient dielectric ring gate insulating matrix is composed of the following components by mass percentage: 84.3485% vinyl-terminated polydimethylsiloxane, 4.5% fumed silica, 3% polymethylhydrosiloxane, 2.5% perfluorodecyltrimethoxysilane, 0.0015% caster platinum catalyst, 0.15% 1-ethynyl-1-cyclohexanol, 1.5% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 1% tris(2,4-di-tert-butylphenyl) phosphite.
3. The high-voltage insulated FPC for battery management according to claim 1, characterized in that, The method for preparing the gradient dielectric ring gate insulating substrate includes the following steps: A1: Vinyl-terminated polydimethylsiloxane is placed in a vacuum drying oven at a temperature of 80-100℃ and a vacuum of -0.08 to -0.10 MPa for 4-6 hours to obtain dried vinyl-terminated polydimethylsiloxane. Fumed silica is placed in a vacuum drying oven at a temperature of 100-120℃ and a vacuum of -0.08 to -0.10 MPa for 4-6 hours to obtain dried fumed silica. Polymethylhydrosiloxane is placed in a vacuum drying oven at a temperature of 60-80℃ and a vacuum of -0.08 to -0.10 MPa for 4-6 hours to obtain dried polymethylhydrosiloxane. 1-Ethynyl-1-cyclohexanol is placed in a vacuum drying oven at a temperature of 40-60℃ and a vacuum of -0.08 to -0.10 MPa for 2-4 hours to obtain dried 1-ethynyl-1-cyclohexanol. A2: Add dried vinyl-terminated polydimethylsiloxane and dried fumed silica to a planetary mixer, set the stirring speed to 500-800 rpm, and the stirring time to 10-15 min to obtain a silicone rubber base material. Then add dried polymethylhydrosiloxane, Castel platinum catalyst, dried 1-ethynyl-1-cyclohexanol, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl) phosphite to the planetary mixer, set the stirring speed to 800-1200 rpm, and the stirring time to 20-30 min. After stirring, vacuum degassing is performed for 10-15 min under a vacuum degree of -0.08 to -0.10 MPa to obtain a liquid silicone rubber premix. A3: Liquid silicone rubber premix is evenly coated onto the surface of release PET film using a precision scraper. The scraper gap is set to 0.3-0.5mm, and the scraper speed is 1-3m / min. After coating, the coated film is sent into a multi-stage hot air oven for gradient pre-curing. The temperature of the first stage is set to 80-90℃ and the dwell time is 5-8min; the temperature of the second stage is set to 100-110℃ and the dwell time is 5-8min; and the temperature of the third stage is set to 115-125℃ and the dwell time is 5-9min. A transition zone with a length of 20-30cm is provided between each stage. After gradient pre-curing, the coated film is allowed to cool naturally to room temperature. The release PET film is then peeled off to obtain a transparent silicone rubber film with a thickness of 0.3-0.5mm. A4: A transparent silicone rubber film is laid flat on a laser processing platform. A high-precision hollowing process is performed using an ultraviolet picosecond laser. The laser wavelength is set to 355nm, the pulse width to 10-15ps, the repetition frequency to 500-800kHz, and the cutting speed to 300-600mm / s. The laser focus is set on the middle plane of the transparent silicone rubber film in the thickness direction to process a concentric ring grid pattern. The ring grid consists of three concentric rings with a width of 0.15-0.25mm and a spacing of 0.4-0.7mm. Each concentric ring is connected and fixed to the others by four connecting bridges that are symmetrically distributed at 90°. The connecting bridges connect local areas of adjacent ring grids. The remaining areas between adjacent ring grids, except for the connecting bridges, are hollow ring grid grooves. After processing, the processing surface is blown with compressed air of 0.3-0.5MPa to remove processing debris, and a ring grid structure silicone rubber matrix is obtained. A5: The ring-grid structure silicone rubber substrate is placed in a plasma treatment device, and the surface of the ring-grid structure silicone rubber substrate is cleaned and activated online using low-pressure plasma in an argon-oxygen mixed atmosphere. The treatment power is set to 200-400W, the argon flow rate is 80sccm, the oxygen flow rate is 20sccm, the treatment pressure is 20-50Pa, and the treatment time is 60-120s to obtain a surface-activated ring-grid structure silicone rubber substrate. A6: Add perfluorodecyltrimethoxysilane to anhydrous ethanol and stir at 300 rpm for 15 min. Then add deionized water and continue stirring and hydrolyzing for 30-60 min while maintaining the stirring speed to obtain a substrate surface treatment solution. The mass ratio of perfluorodecyltrimethoxysilane, anhydrous ethanol and deionized water is 2:90:
8. Let the substrate surface treatment solution stand at room temperature for 30-60 min to obtain an aged substrate surface treatment solution. A7: Immerse the surface-activated ring-gate structure silicone rubber matrix in an aging substrate surface treatment solution. Set the immersion temperature to 25-35℃ and the immersion time to 60-120s. After immersion, place the ring-gate structure silicone rubber matrix in an oven and set the temperature to 100-120℃. Dry and cure for 30-45min to obtain a surface-fluorinated ring-gate structure silicone rubber matrix. Place the surface-fluorinated ring-gate structure silicone rubber matrix in a vacuum oven and set the temperature to 120-140℃, the vacuum degree to -0.08 to -0.10MPa, and the curing time to 30-45min. After curing, allow it to cool naturally to room temperature in the oven to obtain a gradient dielectric ring-gate insulating matrix.
4. The method for preparing a high-voltage insulated FPC for battery management according to claim 1, characterized in that, Includes the following steps: S1: Select an FPC circuit substrate, lay the FPC circuit substrate flat on the inspection table, and check the integrity of the circuit and surface defects under an inspection light source with an illuminance of 1200lx. After confirming that there are no open circuits, short circuits and residual copper defects, place the FPC circuit substrate in a plasma treatment device. Use argon-oxygen mixed atmosphere low-pressure plasma to perform online cleaning and activation treatment on the high-voltage pads and surrounding areas of the FPC circuit substrate surface. Set the treatment power to 200-400W, argon flow rate to 80sccm, oxygen flow rate to 20sccm, treatment pressure to 20-50Pa, and treatment time to 60-120s to obtain a surface-activated FPC substrate. S2: Immerse the surface-activated FPC substrate in an anhydrous ethanol solution containing 1 wt% perfluorodecyltrimethoxysilane for 60 seconds. After immersion, place the surface-activated FPC substrate in an oven and set the temperature to 100-120℃ for drying and curing for 30-45 minutes to obtain the interface-activated FPC substrate. S3: The gradient dielectric ring gate insulating substrate is precisely aligned and placed on the high voltage pad of the interface activated state FPC substrate using an automatic mounting equipment. During placement, ensure that the geometric center of the gradient dielectric ring gate insulating substrate coincides with the geometric center of the high voltage pad. The alignment accuracy is controlled within ±25um. After mounting, let it stand at room temperature for 5-10 minutes to obtain the pre-assembled body. S4: Add the inner layer stress buffer high-K dielectric slurry, the middle layer ring grid filling dielectric slurry, and the outer layer shielding connection conductive slurry to the three independent storage tanks of the three-channel vacuum potting equipment. Set the temperature of the storage tanks to 25-35℃. Perform vacuum degassing on each slurry for 20-30 minutes under a vacuum degree ≤100Pa. After degassing, place the pre-assembled part into the potting chamber of the vacuum potting equipment. Set the vacuum degree of the potting chamber to ≤100Pa to obtain the component to be potted. S5: Vacuum potting is performed on the component to be potted. First, the inner layer stress-buffering high-K dielectric slurry is injected into the central area of the gradient dielectric ring grid insulating substrate through the first channel precision dispensing head. The dispensing pressure is set to 0.1-0.3MPa, and the dispensing time is 3-8s. After injection, it is allowed to stand for 5-10 minutes. Then, the middle layer ring grid filling dielectric slurry is injected sequentially into the inner ring grid groove, middle ring grid groove, and outer ring grid groove of the gradient dielectric ring grid insulating substrate through the second channel micro-dispensing system. The dispensing pressure is set to 0.08-0.2MPa. After each ring grid groove is injected, it is allowed to stand for 2-4 minutes. Finally, the outer layer shielding connection conductive slurry is injected into the gradient dielectric through the third channel precision dispensing head. For the lead-out connection area of the outermost ring gate of the ring gate insulating substrate, the dispensing pressure is set to 0.1-0.3MPa and the dispensing time is 2-5s. The lead-out connection area is located outside the outermost ring gate. A reference ground pad is provided on the FPC circuit substrate directly below the lead-out connection area. The gradient dielectric ring gate insulating substrate has a vertical through hole in the lead-out connection area. The vertical through hole penetrates the thickness direction of the gradient dielectric ring gate insulating substrate. The outer layer shielding connection conductive paste fills the reference ground pad on the surface of the FPC circuit substrate through the vertical through hole to form a vertical electrical connection path. After potting, it is left to stand for 10-15 minutes under a vacuum degree ≤100Pa to obtain the potted FPC component. S6: Transfer the potted FPC component to an oven for low-temperature thermal curing. Set the curing temperature to 130-150℃ and the curing time to 1-2 hours. After curing, allow the FPC component to cool naturally to room temperature in the oven at a rate of 3-6℃ / min. Remove the component after cooling to below 50℃ to obtain the cured FPC component. S7: Lay the cured FPC module flat on the inspection table and check the surface flatness of the insulation structure, the quality of the interface bonding, and the integrity of the ring grid structure under an inspection light source with an illuminance of 1200lx. After confirming that there are no bubbles, delamination, or broken ring defects, immerse the cured FPC module as a whole in perfluorodecyltrimethoxysilane hydrolysate. The perfluorodecyltrimethoxysilane hydrolysate is prepared by perfluorodecyltrimethoxysilane, anhydrous ethanol, and deionized water in a mass ratio of 2:90:
8. The immersion time is 60-120s. After immersion, dry and cure at 100-120℃ for 30-45min to form a hydrophobic shielding layer on the outer surface of the encapsulation structure, thus obtaining a high-voltage insulated FPC for battery management.
5. The high-voltage insulated FPC for battery management according to claim 2, characterized in that, The vinyl-terminated polydimethylsiloxane has a viscosity of 5000 mPa·s and a vinyl content of 0.3 mmol / g.
6. The high-voltage insulated FPC for battery management according to claim 2, characterized in that, The hydrogen content of the polymethylhydrosiloxane is 0.3 wt%.
7. The method for preparing a high-voltage insulated FPC for battery management according to claim 4, characterized in that, The high-K medium slurry for inner layer stress buffer described in step S4 is composed of the following components by mass percentage: 47.8485% vinyl-terminated polydimethylsiloxane, 7% polymethylhydrosiloxane, 38% barium titanate submicron powder with an average particle size of 300 nm and a tetragonal phase, 3.5% fumed silica, 0.0015% caster platinum catalyst, 0.15% 1-ethynyl-1-cyclohexanol, 2% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 1% tris(2,4-di-tert-butylphenyl) phosphite.
8. The method for preparing a high-voltage insulating FPC for battery management according to claim 4, characterized in that, The intermediate ring grid filling medium slurry described in step S4 consists of the following components by mass percentage: 53.3485% vinyl-terminated polydimethylsiloxane, 6% polymethylhydrosiloxane, 29% fumed silica, 4% precipitated silica, 0.0015% caster platinum catalyst, 0.15% 1-ethynyl-1-cyclohexanol, 2.5% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 1% tris(2,4-di-tert-butylphenyl) phosphite.
9. The method for preparing a high-voltage insulated FPC for battery management according to claim 4, characterized in that, The outer shielding conductive paste described in step S4 consists of the following components by mass percentage: 48.3485% vinyl-terminated polydimethylsiloxane, 6% polymethylhydrosiloxane, and 40% flake silver powder, with an average particle size of 10 μm and a tap density of 4 g / cm³. 3 The composition includes flake silver powder, 3.5% fumed silica, 0.0015% castor platinum catalyst, 0.15% 1-ethynyl-1-cyclohexanol, 1% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 1% tris(2,4-di-tert-butylphenyl) phosphite.